Pemberdayaan Masyarakat melalui Pemanfaatan Botol Bekas untuk Pengendalian Hama Lalat Buah - Syuhada, Ammar Fatwa; Santosa, Mohammad Rizky Nur; Ramadhan, Andhika Putra; Agraini, Fitria Kusuma; Carera, Silviana Chandra; Abdillah, Annisa Jasminna; Fayyidillah, Bagas Adi; Pramudya, Bramanta Eka; Rielies, Noer Fadilla Sapoetri; Astuti, Yoni (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
This community service program was carried out by the team of Muhammadiyah University of Yogyakarta (UMY) with the aim of helping the people of Padukuhan Dukuhsari, Wonokerto Sub-district, Turi District, Sleman Regency, in overcoming the problem of fruit fly pests that threaten salak plants. This problem originated from the high level of salak fruit damage caused by the fruit fly pest Bactrocera dorsalis. This pest attacks plants by laying eggs inside the fruit, which then hatch into larvae and damage the fruit from the inside. This condition has a significant impact on reducing the yield of salak farmers in the region.Overcoming this problem, the UMY team initiated an environmentally friendly innovation-based community empowerment program by utilizing used bottles as fruit fly traps. This program involves three main stages, namely socialization, training, and evaluation. At the socialization stage, the community gained an understanding of the characteristics of fruit fly pests, their impact on salak plants, and how to effectively control them. The training was followed by the practice of making traps using key materials such as used bottles, petrogenol as an attractant, insecticide, and insecticidal adhesive as a binding agent. The traps were designed to be installed at various strategic points in the salak orchard.The evaluation was conducted by monitoring the number of fruit flies trapped for six days in five different locations. The results showed that the location with the highest number of trapped fruit flies was Kebun Salak Belakang Pendopo more than 41%, which is thought to have many alternative host plants for the pest. Weather factors and food availability also affected the number of flies captured. The program received a positive response from the community, who enthusiastically participated in the socialization activities and trap-making practices. With this innovation, it is hoped that the community can reduce dependence on excessive chemical pesticides, increase salak yields, and utilize plastic waste effectively to support sustainable agriculture